ISLAM AND CULTURAL ACCULTURATION IN THE BARONG TRADITION OF THE OSING BANYUWANGI COMMUNITY - Rachel Nazla; Rozaqul Arif (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2025)
This study explains the form of acculturation of Islamic values in the Barong Ider Bumi tradition in Kemiren Village, Banyuwangi. The Barong tradition was initially strong with animistic values, but Islam is dialectic which makes this tradition undergo an adjustment in meaning and value. This study uses a descriptive qualitative method with an ethnographic approach. The results of the research show that the acculturation of Islamic values in the Barong tradition can be seen in its rituals with Islamic nuances, the transformation of the meaning of earth alms as a pious deed, and Barong as a mystical symbol to be religious. The values of cultural da'wah are manifested through the involvement of religious leaders in directing the spirituality of the community to remain in accordance with the teachings of monotheism.